2017
DOI: 10.1016/j.bjid.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Infections after shoulder arthroplasty are correlated with higher anesthetic risk score: a case-control study in Brazil

Abstract: This study provides evidence suggesting that patient-related known factors such as higher ASA score predisposes to shoulder arthroplasty-associated infection. Furthermore, unusual pathogens associated with PSI were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
0
21
0
5
Order By: Relevance
“…,Gao et al (2010),Gil-Londoño et al (2016),Giri et al (2008),Hafez et al (2012),Hao et al (2013),Hernaiz-Leonardo et al (2017),Hey et al (2017),Ibrahim et al (2014),Jyothirmayi et al (2017),Kanafani et al (2006),Khan et al (2010),Khan et al (2011),Ledur et al (2011),Lee et al (2007),Lee et al (2010),Lee et al (2015),Legesse Laloto et al (2017),Leon et al (2011),Li et al (2013),Liu et al (2017),Lyimo et al (2013),Madu et al (2011), El Maerrawi and Carvalho (2015),Malik et al (2009),Martins et al (2008),Marwa et al (2015),Mathur et al (2013),Mawalla et al (2011),Mehrabi Bahar et al (2015),Memon et al (2013),Mundhada and Tenpe (2015),Nagaya et al (2017),Ng et al (2015),Ning et al (2014),Nwankwo and Edino (2014),Oliveira and Carvalho (2004),Pardhan et al (2013), Porras-Hernandez et al (2008,Portillo-Gallo et al (2014),Qi et al (2013),Qin et al (2014),Qiu et al (2011),Rabiu ...…”
mentioning
confidence: 99%
“…,Gao et al (2010),Gil-Londoño et al (2016),Giri et al (2008),Hafez et al (2012),Hao et al (2013),Hernaiz-Leonardo et al (2017),Hey et al (2017),Ibrahim et al (2014),Jyothirmayi et al (2017),Kanafani et al (2006),Khan et al (2010),Khan et al (2011),Ledur et al (2011),Lee et al (2007),Lee et al (2010),Lee et al (2015),Legesse Laloto et al (2017),Leon et al (2011),Li et al (2013),Liu et al (2017),Lyimo et al (2013),Madu et al (2011), El Maerrawi and Carvalho (2015),Malik et al (2009),Martins et al (2008),Marwa et al (2015),Mathur et al (2013),Mawalla et al (2011),Mehrabi Bahar et al (2015),Memon et al (2013),Mundhada and Tenpe (2015),Nagaya et al (2017),Ng et al (2015),Ning et al (2014),Nwankwo and Edino (2014),Oliveira and Carvalho (2004),Pardhan et al (2013), Porras-Hernandez et al (2008,Portillo-Gallo et al (2014),Qi et al (2013),Qin et al (2014),Qiu et al (2011),Rabiu ...…”
mentioning
confidence: 99%
“…The formation of hematoma or postoperative drainage for more than 2.5 days following arthroplasty has been identified previously as a predictor of wound infection for patients receiving hip and knee joint replacements [30]. In shoulder arthroplasty, an association between postoperative hematoma and subsequent PJI was documented by Cheung et al [31] and Nagaya et al [6]. Cheung et al [31] identified various species of skin-associated microbiota in hematoma cultures, including Cutibacterium acnes, Staphylococcus epidermidis and other Streptococcus spp.…”
Section: Discussionmentioning
confidence: 97%
“…However, prosthetic joint infection (PJI) is among the most feared complications that may result from such procedures, with an incidence of 1% to 2% among primary [1,2] and up to 4% among revision arthroplasties [3,4], respectively. Older patient age, revision arthroplasty, diabetes mellitus, rheumatoid arthritis, smoking, obesity and a high American Society of Anaesthesiologists (ASA) score are viewed as independent risk factors (RFs) for PJI [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-positive cocci (GPC), such as Staphylococcus aureus and coagulase-negative Staphylococci, are the major PJI-related microorganisms, followed by Gram-negative bacilli (GNB), with a prevalence ranging from 5 to 23% [4][5][6]. In some case series, PJIs attributed to GNB have been reported at rates greater than 40% [7,8].…”
Section: Introductionmentioning
confidence: 99%